The Optimization of a Spray Gel : Formula with Acalypha Leaf Extract (Acalypha wilkesiana Müell. Arg.) - Galuh Maulidatun Nufus; Nafisah Isnawati (LPPM Universitas dr. Soebandi, 2025)
Background: According to research from the Ministry of Health, in 2020 the average was 89.65% and in East Java it was 54.3%, while in Jember 49.6% of people washed their hands properly, one of which was using soap. Hand sanitizer can be used as an alternative to cleaning hands without using soap and running water. One of the plants used as an active ingredient in hand sanitizers is akalifa leaves. Carbopol 940 is a gelling agent that is widely used in spray gel preparations for pharmaceutical products, while TEA is an alkalizing agent. Objective: To identify the effect of carbopol 940 as a gelling agent and TEA as an alkalizing agent on the physical characteristics of akalifa leaf extract spray gel (Acalypha wilkesiana Müell. Arg.). Methods: This study used an experimental method with the Simplex Lattice Design. Research result: Evaluation of the physical properties of spray gel preparations with variations in the concentration of the gelling agent and alkalizing agent produced the best pH value, namely in formula 2 with a pH value of 5.2, the best viscosity value was found in formula 2, namely with a value of 223 cPs, and drying time the best is also found in formula 2 with a value of 3.35 minutes. Conclusion: evaluation of the physical properties of spray gel preparations, variations in the concentration of the gelling agent and alkalizing agent affect pH, viscosity, spraying pattern and drying time.